2018
DOI: 10.1108/ijopm-12-2016-0705
|View full text |Cite
|
Sign up to set email alerts
|

Natural disasters, PC supply chain and corporate performance

Abstract: Purpose -This paper provides quantitative evidence of natural disasters' effect on corporate performance and studies the mechanisms through which the supply chain moderates and mediates the link. Design/methodology/approach -Using two major natural disasters as quasiexperiment, namely the 2011 Japanese earthquake-tsunami (JET) and Thai flood (TF), and data over the period 2010Q1-2013Q4, effect of these events on end assemblers' performance is studied, with a focus on the personal computer (PC) supply chain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 26 publications
1
47
0
1
Order By: Relevance
“…The former is normally manageable through routine business functions and processes, while the latter can lead to unexpected disruptions to normal business operations (Fiksel, 2015, p. 12). In the extreme there is the highly unpredictable but impactful events that are disruptive to the supply chain and business functions of an enterprise (Gunessee et al, 2018;Knemeyer et al, 2009;Simchi-Levi et al, 2014). through its 'lack of clarity' due to possible multiple sometimes conflicting meanings that can be given to the data; or through the newness of the situation such as lack of signals (Budner, 1962).…”
Section: Typology Of Ambiguitymentioning
confidence: 99%
“…The former is normally manageable through routine business functions and processes, while the latter can lead to unexpected disruptions to normal business operations (Fiksel, 2015, p. 12). In the extreme there is the highly unpredictable but impactful events that are disruptive to the supply chain and business functions of an enterprise (Gunessee et al, 2018;Knemeyer et al, 2009;Simchi-Levi et al, 2014). through its 'lack of clarity' due to possible multiple sometimes conflicting meanings that can be given to the data; or through the newness of the situation such as lack of signals (Budner, 1962).…”
Section: Typology Of Ambiguitymentioning
confidence: 99%
“…In total, 141 studies from our sample (155) implied four drivers of resistance, comprising: agility, visibility, robustness, and velocity (Table I). Three of the four drivers are widely discussed in the extant literature with considerable empirical and theoretical work, including: visibility (49 studies e.g., Peck, 2005;Ivanov and Sokolov, 2013;Dubey et al 2018b), robustness (43 studies e.g., Brandon-Jones et al, 2014;Gunessee et al, 2018), and agility (40 studies e.g., Blackhurst et al, 2005;Wieland and Wallenburg, 2013;Yang and Hsu, 2018). However, the last driver-velocity (9 studies e.g., Peck, 2005;Fiksel et al, 2015;Kwak et al, 2018)-has received scant attention in terms of the total number of studies and empirical validation, alike.…”
Section: Analysis and Synthesis Of Findingsmentioning
confidence: 99%
“…This study contributes to research streams in the areas as diverse as DCV, SC-Ambidexterity and SC-Resilience. Prior research has shown that dynamic capabilities are necessary to achieve SC-Resilience (Gunessee et al , 2018). Thus, by suggesting a supply chain-related capability (i.e.…”
Section: Introductionmentioning
confidence: 99%